Efektifitas terapi acupressure pada telapak kaki terhadap sensitivitas kaki pada pasien diabetes melitus tipe ii. - -, Darmilis -; Hasneli, Yesi -; Indriati, Ganis - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of the research is to analize the effect of acupressure therapy on the level of foot sensitivity in diabetic patients. The research used quasy experiment  design with  non-equivalent control group which divided into experimental group and control group. Sample of this research is 30 people divided into15 people as the experimental group and 15 people as a control group. Instruments of this research using monofilament in both groups to measuring respondent foot sensitivity. The experimental group were given intervention with acupressure therapy three times in 1 week. Data then analyzed into univariate and bivariate using independent t test dan dependent t test. The result of the research showed that mean level of foot sensitivity before acupressure therapy  was  5.93 points  and  mean  level  of  foot  sensitivity  after  acupressure therapy was 7.14 poin. There is increase in the foot sensitivity after given intervention with p value 0,000 (<0,05). And it’ mean that acupressure therapy are effective against increasing the foot sensitivity.   Keywords: Diabetes mellitus, Foot sensitivity, Acupressure therapy.